Imitative approach to medical training - V. G. Pinkas; O. A. Toporkova; I. М. Kuvichka (Zaporozhye State Medical University, 2014)
This article examines the use of modern information technology, namely the imitative modeling, in medical students' training. The imitation system of the educational process has been described and the characteristic of the basic didactic principles in imitative approach to the medical education has been provided.